Do bureaucracies enhance or constrain policy effectiveness? Evidence from Turkey's central management of public investment - Davide Luca (London School of Economics and Political Science (LSE), European Institute, 2016)
Despite a significant amount of research, literature continues to produce contrasting predictions on how, and when, public bureaucracies may enhance or constrain policy effectiveness. On the one hand, developmental state research has stressed the importance of bureaucrats' autonomy from politics, particularly in emerging economies. On the other hand, public choice literature has called for strong oversight by politicians over the bureaus. The paper contributes to this debate by analysing Turkey's contemporary public investment management. It offers a detailed exploration of how economic bureaucracy's characteristics contributed to 'sound' investment management. The analysis draws on in-depth elite interviews. The results suggest that the existence of a capable and authoritative organisation directing the project cycle has positively contributed to the technical management of investments. Empirical evidence also indicates that this organisation is insufficiently insulated vis-à-vis government; its ability to implement 'sound' policies is therefore contingent on the political context. Nevertheless, the analysis also uncovers significant resistance of the bureaucrats against measures which would increase bureaucratic efficiency and transparency. Overall, the findings suggest that bureaucratic autonomy and accountability play an equally relevant role in determining policy effectiveness.
Keywords: 330; bureaucracies; policy effectiveness; public goods; EU Candidate Countries; Turkey